Enhanced photoluminescence of potassium-doped tungsten oxide by acetone exposure. Issue 2 (4th January 2023) - Patel, Aman; Lu, Weigang; Birmingham, Blake; Johnson, Michael; Wang, Danling; Zhang, Zhenrong; Wang, Kai
Abstract : Studies of optical properties of doped nanocrystals of tungsten trioxide can elucidate new information about the material. Abstract : Studies of optical properties of doped nanocrystals of tungsten trioxide can elucidate new information about the material. A novel molecule-enhanced photoluminescence (PL) of potassium-doped tungsten trioxide (K x WO) was explored in the presence of different gases to understand charge transfer between molecules and K x WO on the properties of the material. We performed Raman spectroscopy and PL experiments in the presence of gaseous acetone or ethanol mixed with other gases (N2 and O2 ). PL at 630 nm from K x WO was observed and further enhanced when the sample was continuously irradiated with a 532 nm CW laser in acetone. A mechanism of strong emission of the PL induced by the charge transfer between the acetone and the K x WO is proposed.